Copper-Catalyzed Ring Expansion of Vinyl Aziridines under Mild Conditions - Tosi, Eleonora; Spielmann, Kim; de Figueiredo, Renata Marcia; Campagne, Jean-Marc (Synlett, 2021)
Vinyl aziridines are versatile starting materials toward ring-expansion transformations. Such processes are widely used to give various medium or larger N-heterocycles of synthetic interest. This letter describes a copper-catalyzed ring expansion of vinyl aziridines to 3-pyrrolines by using a Cu(I) salt [(CuOTf)2·toluene or Cu(MeCN)4·PF6]. In particular, this transformation occurs under mild conditions (THF, rt).
Keywords: ring expansion; vinyl aziridines; pyrrolines; copper catalysis; heterocycles